PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 51 PEKANBARU - Zam, Randy; Antosa, Zariul; Witri, Gustimal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research was the low student learning outcomes IPS, this happens because the methods are not diverse and the learning process is only centered on the teacher so that make students have a passive nature and difficult to solve problem about IPS. It is necessary for research to improvements in the learning process through the implementation of cooperative learning model type think pair share (TPS). The study design using the PTK (classroom action research) that the implementation is done two cycles, each cycle there are two meetings with the daily test. Data obtained from the observation of teacher activity using observation sheet teacher activity, student activity observation using observation sheet student activity. The subjects were students of class Vb SDN 51 Pekanbaru totaling 30 people. Data collection instrument in this paper is a sheet activities of teachers, student activity sheets, and the sheet of daily test. This questions in the daily tesy consisted of 20 items objective for every cycle. The results showed that the learning outcomes of students increased from prior courses of action with an average of 65,13 increased in the first cycle to 73,50. In the second cycle increased into 84,17. The increased of learning oucomes from base score to UH I is 12,85% while at the second daily test so increased become 29,23%. Based on these results, it can be concluded that the implementation of cooperative learning model types think pair share can improve learning outcomes IPS Class V SDN 51 Pekanbaru.Keywords : Cooperative Learning Model Type Think Pair Share, Learning Outcomes IPS.